The impact of trammel nets as an MPA soft bottom monitoring method. (January 2021) - Priester, C. Robert; Martínez-Ramírez, Lucas; Erzini, Karim; Abecasis, David
Highlights: Impact quantification of trammel net monitoring of soft-bottom fish community in a MPA. Case study in Prof. Luiz Saldanha Marine Park, Arrabida, Portugal. High catch per unit effort with low selectivity and low mortality of target and protected species. Trammel nets good fisheries independent monitoring method for low-visibility soft-substrate fish communities. Abstract: With the global increase of marine protected area (MPA) implementation, the need for monitoring and the evaluation of their effectiveness becomes ever more important. Currently there is a severe lack of information about the protection effects of soft-substrate ecosystems. While many different methods have been established for the monitoring of hard-substrate ecosystems, most of these minimally invasive methods prove ineffective for soft- bottom habitats. Information and quantification of the impact of monitoring methods is needed to provide decision makers with the necessary knowledge to choose appropriate and feasible monitoring methods. In this study we quantify the impact of experimental trammel net fishing as a monitoring method of the soft-substrate demersal fish community using the Arrábida MPA (Portugal) as a case study. Over the 14 biannual sampling campaigns (between 2010 and 2019) 21, 873 individuals and 5.61 tonnes of fish were caught. The gear is highly effective with an average catch per unit effort higher than reported for commercial fisheries in adjacent areas. When excluding the pelagic species, mortality rates are 41.2% and 30.4% in numbers and biomass, respectively. Most of the dead individuals belong to small, non-protected species with relatively little commercial value while MPA conservation target groups such as Soleidae and Rajidae have high survival rates. Due to its low size- and species-selectivity and the high survival rate of protected valuable species, the trammel net experimental fishing proved to be an effective monitoring method for soft-substrate demersal fish communities. Given their relatively low impact on the local ecosystem experimental trammel nets are a good alternative for areas where non-extractive methods are not effective. Nevertheless, quantification of the impact of other monitoring methods is necessary to enable the determination of the methods with the lowest mortality and impact for future soft-substrate MPA monitoring.